Confrontation and cooptation: A brief history of Australian political blogs - Highfield, Tim; Bruns, A. (2012)
Even early on, political blogging in Australia was not an entirely alternative endeavour - the blogosphere has seen early and continued involvement from representatives of the mainstream media. However, the acceptance of the blogging concept by the mainstream media has been accompanied by a comparative lack of acceptance of individual bloggers. Analyses and commentary published by bloggers have been attacked by journalists, creating an at times antagonistic relationship. In this article, we examine the historical development of blogging in Australia, focusing primarily on political and news blogs. We track the evolution of individual and group blogs, and independent and mainstream media-hosted opinion sites, and the gradual convergence of these platforms and their associated contributing authors. We conclude by examining the current state of the Australian blogosphere and its likely future development, taking into account the rise of social media, particularly Twitter, as additional spaces for public commentary.